PENGELOLAAN ARSIP UNTUK KETERTIBAN ADMINISTRASI DI KANTOR KALURAHAN WUKIRSARI KAPANEWON IMOGIRI KABUPATEN BANTUL - Reziana, Risna; Wijayanti, Bernadeta Nefo Eka (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
Archives are evidence and records of activities, from creation to decision making, which have important value for government administration. The Wukirsari Village Office, Kapanewon Imogiri, Bantul Regency was chosen as the research location because of problems in archival management. Initial observations showed that archive management was not in an orderly manner in terms of storage and arrangement. This research aims to describe archive management and the factors causing the lack of orderly management of archives, for administrative order at the Wukirsari Village office, Kapanewon Imogiri, Bantul Regency. The research method is descriptive qualitative with data collected through interviews, observation and documentation. The results of the research show that archive management at the Wukirsari District Office is not yet orderly, even though Bantul Regent Regulation Number: 139 of 2022 has been implemented regarding Archive Classification Codes within the Bantul Regency Government.Â  In the process of implementing the electronic Surat Bantul (e-surban) application, archive management training has been held. The factors causing deficient records management are lack of attention to records maintenance, limited facilities, lack of understanding of technology among employees, difficulty adapting to technology, and the absence of a policy and schedule for records depreciation.Keyword: Archives Management; Administrative Order.